MATHEMATICS STUDIES AT UNIVERSITY : EFFECT ON THE PROFESSIONAL COMPETENCE - Vintere, Anna; Zeidmane, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
It is known that mathematics has an impact on the development of the professional competence both directly (serves as a tool for solving and calculating various problems) and indirectly (promotes logical thinking, develops skills to formulate and solve problems etc.). To identify importance of mathematics studies in the development of professional competence in assessment of graduates the research was done by Latvian University of Agriculture and Siauliai University in the framework of Latvian-Lithuanian cross-border cooperation program‘s project „Cross-border network for adapting mathematical competences in the socio-economical development”. A questionnaire based research was the part of this research. The survey results obtained in Latvia are analysed in this article and include the following aspects: mathematics in professional practice and need for improvement of mathematical knowledge and assessment of practical potential of mathematics.